A highly sensitive fluorescence probe for thiophenol in living cells via a substitution-cyclization strategy. Issue 39 (27th September 2019) - Yang, Linlin; Liu, Yang; Li, Yanping; Wang, Hao; Zhang, Haihua; Xu, Jinhe; Ji, Liguo; Wang, Qingzhi; He, Guangjie
Abstract: A novel fluorescent probe1 was synthesized for the detection of thiophenol on the basis of a unique thiophenol-mediated substitution-cyclization reaction. The probe1 displayed 420-fold fluorescence intensity enhancement and highly selective and sensitive response for thiophenol over other competing sulfur species. This probe showed an excellent linear relationship in 10–140 μM and the low detection limit of 29 nM. The recognition mechanism of probe1 toward PhSH was supported by the NMR spectrum and ESI-MS. Furthermore, the probe1 was successfully applied for detection of thiophenol in living HepG2 cells. Graphical abstract: Image 1 Highlights: A novel fluorescent probe1 for thiophenol was constructed on the basis of substitution-cyclization reaction. Probe1 features significant fluorescence enhancement up to 420-fold in response to thiophenol in aqueous solution. This probe showed an excellent and wide linear relationship in 10–140 μM and with a low detection limit of 29 nM. The probe could detect thiophenol in living cells.